Larvas de Anopheles (subgênero Kerteszia) Theobald 1905 encontradas em criadouros artificiais, no Estado do Paraná, Brasil Larvas of the Anopheles (sub-genus Kerteszia) Theobald 1905, found in artificial breeding pens, in the State of Paraná, Brazil - Ennio Luz; José Consolim; Orlando Carlos Barbosa; Pedro Barroso Torres (Universidade de São Paulo, 1987)
Discute-se encontro de larvas de duas espécies de anofelinos do subgênero Kerteszia - An. (Ker.) cruzii e An. (Ker.) bambusicolus - em criadouros artificiais, no Estado do Paraná, Brasil. The finding of larvas of two species of anofelini (Kerteszia) An. (Ker.) cruzii and An. (Ker.) bambusicolus in artificial breeding pens, in the state of Paraná, Brazil, is discussed.